Neem (Azadirachta indica A. Juss.) - a Versatile Multipurpose Tree - Biswas, S.A.S.; Singh, Paramjit; Chandra, Sumer (Indian Forester, 1995)
Neem (Azadirachta indica A. Juss.) is one of the most valuable multipurpose species and its potential has been least exploited. Tree is an outstanding example of the species which is higbly efficient not only in restoring soil productivity but also in providing fodder, fuelwood and other value-added products like medicines, pesticides, mosquito repellent, fertilizers, soaps, lubricants, gums and even contraceptives. Neem is considered as a "wonder tree for the future" for the developing Third World countries in their reforestation and environmental restoration programmes and for providing useful products. Paper comprehensively also outlines the research needs and priorities on the species in terms of utilitarian aspects.